Bibliometric study on scientific production in the field of educational technology - Castellanos Ramírez, Juan Carlos; Parra Encinas, Karla Lariza (TECHNO REVIEW. International Technology, Science and Society Review /Revista Internacional de Tecnología, Ciencia y Sociedad, 2023)
This paper analyzes the scientific production published by three journals focused on Educational Technology (ET). A bibliometric study was carried out considering indicators of production, authorship and thematic lines developed between 2011 and 2021. The results highlight that the current production of articles on ET is greater than a decade ago and is mainly generated by researchers from Spanish and Mexican universities. The scientific production has been developed around 13 thematic lines. As can been seen, some thematic lines demand more attention and coverage within the research agenda.